2023
DOI: 10.3389/fgene.2022.1022626
|View full text |Cite
|
Sign up to set email alerts
|

High expression of RNF169 is associated with poor prognosis in pancreatic adenocarcinoma by regulating tumour immune infiltration

Abstract: Background: Pancreatic adenocarcinoma (PAAD) is a highly deadly and aggressive tumour with a poor prognosis. However, the prognostic value of RNF169 and its related mechanisms in PAAD have not been elucidated. In this study, we aimed to explore prognosis-related genes, especially RNF169 in PAAD and to identify novel potential prognostic predictors of PAAD.Methods: The GEPIA and UALCAN databases were used to investigate the expression and prognostic value of RNF169 in PAAD. The correlation between RNF169 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…RNF169 is a 77 kDa protein that contains an N-terminal RING finger motif, a central MIU1 and a C-terminal MIU2 (motif interacting with ubiquitin) domains that recognizes the ubiquitinated histone marks and accumulates near the DNA double strand break (DSB) lesions ( Chen et al, 2012 ; Panier et al, 2012 ; Poulsen et al, 2012 ). The role of RNF169 in development and human disease has not been extensively investigated; it was suggested that that high expression of RNF169 could be a prognostic marker in pancreatic ductal carcinoma although this association has not been experimentally validated yet ( Wang J. et al, 2022 ). Due to its lack of enzymatic activity, RNF169 antagonizes the function of its close homologue RNF168 an active ubiquitin ligase that recognizes the same K13/K15-ubiquitinated H2A and amplifies the DNA damage response by further ubiquitinating its substrates at site of the lesion ( Hu et al, 2017 ; Kitevski-LeBlanc et al, 2017 ; An et al, 2018 ).…”
Section: Understanding the Function And Regulation Of Dyrk1a Through ...mentioning
confidence: 99%
“…RNF169 is a 77 kDa protein that contains an N-terminal RING finger motif, a central MIU1 and a C-terminal MIU2 (motif interacting with ubiquitin) domains that recognizes the ubiquitinated histone marks and accumulates near the DNA double strand break (DSB) lesions ( Chen et al, 2012 ; Panier et al, 2012 ; Poulsen et al, 2012 ). The role of RNF169 in development and human disease has not been extensively investigated; it was suggested that that high expression of RNF169 could be a prognostic marker in pancreatic ductal carcinoma although this association has not been experimentally validated yet ( Wang J. et al, 2022 ). Due to its lack of enzymatic activity, RNF169 antagonizes the function of its close homologue RNF168 an active ubiquitin ligase that recognizes the same K13/K15-ubiquitinated H2A and amplifies the DNA damage response by further ubiquitinating its substrates at site of the lesion ( Hu et al, 2017 ; Kitevski-LeBlanc et al, 2017 ; An et al, 2018 ).…”
Section: Understanding the Function And Regulation Of Dyrk1a Through ...mentioning
confidence: 99%